Al-Amru Fî Al-Lughah Al-‘Arabiyyah Wa Al-Lughah Al-Indûnîsiyyah Dirâsah Taqâbuliyyah Tathbîqiyyah - Atikah Zahroh; Nofa Isman (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
هدفت هذه الدراسة إلى معرفة الأمر في اللغة العربية ونظيرها في اللغة الإندونيسية لاكتشاف أوجه التشابه والاختلاف بينهما من الناحية الصرفية والنحوية والدلالية، ثم إعداد المادة الدراسية لتعليم الأمر في اللغة العربية بناء على نتائج الدراسة. والمنهج الذي استخدمته الباحثة في هذه الدراسة هو المنهج الوصفي التحليلي للوقوف على خصائص الأمر في اللغتين، والمنهج التحليل التقابلي لمقارنة نظام الأمر في اللغتين واستنباط ما فيهما من أوجه التشابة والاختلاف. وقد توصلت هذه الدراسة إلى ثلاث نتائج، هي : 1) وجود 15 وجه التشابه بين الأمر في اللغتين منها: أن فعل الأمر فيهما من الأفعال اللازمة والمتعدية، ووجود 37 وجه الاختلاف منها: نيابة المصدر عن فعل الأمر في العربية وعدمها في الإندونيسية. 2) الصعوبات المتوقع حدوثها نتيجة الاختلاف بين اللغتين، 3) الاستفادة من نتائج الدراسة في إعداد المادة الدراسية لتعليم الأمر في اللغة العربية للمتعلمين الإندونيسيين بوضعها في نصوص الحوار والقراءة والوحدات التعليمية. This study aimed to know the imperative sentence in Arabic and its counterpart in Indonesian language, to discover its similarities and differences from the morphological, grammatical and semantic aspects, then prepare some learning materials to teach it based on the results of the study. The method used in this study is the descriptive analytical approach to determine the properties of the imperative sentences between the two languages, and the cross-analytical approach to compare the rules of both languages, and to infer the similarities and differences between them. This study has reached three results, they are: 1) 15 similarities of the imperative sentence in the two languages, including: imperative verbs between them is formed from intransitive and transitive verbs, and there were also 37 differences, including: the use in masdar (verbal noun) as an imperative word in Arabic, and lack of it in Indonesian. 2) The difficulties may occur as a result of the difference between both languages, 3) Applying the results of the study in preparing learning materials to teach the imperative sentences in Arabic to Indonesian learners by placing them in the texts of dialogue, reading and units.